Measurement of the rotor blade section aerodynamic coefficients by particle image velocimetry - Zanotti, A.; Gibertini, G.; Auteri, F.; Campanardi, G.; Droandi, G; Grassi, D. (My University, 2015)
Particle Image velocimetry surveys were carried out around the blade section at 65% radius of a four-bladed articulated rotor model to evaluate the airloads coefficients from velocity data. The blade section aerodynamic loads were calculated using the control volume approach and compared with the results of the blade element momentum theory in hovering for validation. As the compressibility effects for the present test case are not negligible, the pressure on the contour of the control surface was computed from the measured local velocity using the isentropic relations. The vertical force coefficient calculated from PIV data shows a quite good agreement with blade element theory results. The experimental campaign included also surveys around the blade section equipped with passive Gurney flap with different height. Thus, the method to obtain the aerodynamic loads from PIV data was employed to evaluate the effect of the flap on the vertical aerodynamic force acting on the blade section in hovering.
Keywords: Green Rotorcraft